Ecclesiastic Audio Description: The Church from a Semiotic and Translation Perspective - Lax-López, María (Íkala, Revista de Lenguaje y Cultura, 2023)
Audio description (AD) is a type of accessible translation consisting of a process of intersemiotic translations from images into words. Its objective is, mainly, allowing people with visual disabilities to create a mental image of the things they cannot perceive visually. In this study, we will address a type of AD that has not been explored in academic and professional contexts: church AD, where the source text is the church, understood to be the architectonic structure used for Christian worship. Our aim is to provide a basis for the study and practice of church AD. To this end, we propose three approaches: functional and contextual, semiotic and normative. The first approach describes the different ways in which churches are used today and the context in which the audio described text is produced. The second helps to identify the visual keys that form the church's meaning and to guide the audio describer in selecting translatable information. The last one provides AD guidelines or strategies that can be applied to the submodality of AD analyzed.